Mobility for learners and staff - higher education students and staff mobility inter-institutional agreement 2014-2021 between programme countries – Universitat de València and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2017)
- Cooperate for the exchange of students and/or staff in the context of the Erasmus+ programme. - Subject area: Any.